Penilaian Kinerja Keuangan PT Kereta Api Indonesia (Persero) Periode 2017-2021 (Program Studi Ilmu Administrasi Bisnis, 2023)
One of the things that determines the quality of a company is its financial performance, from its financial performance it can be seen how the company manages finances and carries out its operational activities. Financial performance must be assessed and controlled so that the company always develops in a directed manner. Large companies have an obligation to ensure that their financial performance is in good condition, one of which is BUMN. BUMN companies have a responsibility to the state because in their operational activities they indirectly intersect with the community. One of these state-owned companies is PT Kereta Api Indonesia (Persero), the only state-owned company engaged in transportation with its trains. In Indonesia, trains are a popular form of transportation so that PT KAI's operational activities play a major role in community mobility. Due to its considerable influence, PT KAI has the responsibility to maintain its financial performance. PT KAI's financial performance is assessed using benchmarks in the form of the Decree of the Minister of BUMN Number KEP-100 / MBU / 2002. The results of this assessment of PT KAI's financial performance show that during the 2017-2020 period PT KAI experienced a decline in financial performance, and experienced an increase in financial performance in 2021. Keywords: company, finance, financial performance